1970
DOI: 10.1677/joe.0.0460297
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adrenalectomy in Female Rats on Reproductive Processes Including Effects on the Foetus and Offspring

Abstract: SUMMARY Mating and impregnation were not prevented by adrenalectomy in female rats; they carried their young to term, large litters of viable young were born and lactation was sufficient to maintain the young throughout the usual nursing period. By comparison with sham-operated mother rats, the adrenalectomized mothers gave birth to smaller litters, their pups weighed less and had increased levels of plasma corticosterone. Prenatal and postnatal effects on the offspring were separated by crossf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

1970
1970
2010
2010

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Thoman recently demonstrated that adrenalectomy does not interfere with mating and impregnation and the ability to carry viable litters to term, although litter size was smaller, the pups weighed less, and had higher levels of plasma corticosterone than pups of non-adrenalectomized mothers. Lactation was sufficient to maintain the young (200). Others have supported the ability of adrenalectomized animals to become pregnant (98), and implicated the role of cor-· ticoids in parturition (1).…”
mentioning
confidence: 99%
“…Thoman recently demonstrated that adrenalectomy does not interfere with mating and impregnation and the ability to carry viable litters to term, although litter size was smaller, the pups weighed less, and had higher levels of plasma corticosterone than pups of non-adrenalectomized mothers. Lactation was sufficient to maintain the young (200). Others have supported the ability of adrenalectomized animals to become pregnant (98), and implicated the role of cor-· ticoids in parturition (1).…”
mentioning
confidence: 99%
“…Such rhythms may also exist during pregnancy (Dupouy and Cohen, 1975 Kitay, 1977) or after the administration of synthetic ACTH (Mayer, 1978 (Parvez et al, 1972 ;Yoshinaga, 1978). In the rat, adrenalectomy of the mother leads to an increase of foetal adrenal weight (Ingle and Fisher, 1938 ;Walaas and Walaas, 1944 ;Angervall, 1962 ;Klepac et al, 1977) and to an augmentation in foetal corticosteroid concentrations (Thoman et al, 1970 ;Cohen and Brault, 1974 ;Klepac et al, 1977 ;Arishima et al, 1977). Conversely, the stimulation of maternal corticosteroid secretion reduces the development of foetal adrenal glands (Milkovic and Domac, 1973 ; and decreases their in vitro steroidogenesis (Klepac et al, 1977).…”
mentioning
confidence: 99%
“…Although lactation can proceed in the absence of the adrenals, milk production certainly is not optimal [Thoman et al, 1970b]. Suckling directly stimulates the secretion of ACTH and corticosterone [Voogt et ai, 1969], as well as of prolactin and other pituitary hormones involved in lactation [Meites, 1966].…”
mentioning
confidence: 99%